Humanoid Robot Walking in Maze Controlled by SSVEP-BCI Based on Augmented Reality Stimulus - Zhang, Shangen; Gao, Xiaorong; Chen, Xiaogang (Frontiers in Human Neuroscience, 2022)
The application study of robot control based on brain-computer interface (BCI) not only helps to promote the practicality of BCI, but also helps to promote the advancement of robot technology, which is of great significance. Among the many obstacles, the importability of stimulator brings much inconvenience to the robot control task. In this study, augmented reality (AR) technology was employed as the visual stimulator of steady-state visual evoked potential (SSVEP)-BCI, and the robot walking experiment in the maze was designed to testify the applicability of AR-BCI system. The online experiment was designed to complete the robot maze walking task and the robot walking commands were sent out by BCI system, in which human intentions were decoded by Filter Bank Canonical Correlation Analysis (FBCCA) algorithm. The results showed that all the 12 subjects could complete the robot walking task in the maze, which verified the feasibility of the AR-SSVEP-NAO system. This study provided an application demonstration for the robot control base on brain-computer interface, and further provided a new method for the future portable BCI system.